Utility of Feed Enzymes and Yeast Derivatives in Ameliorating Deleterious Effects of Coccidiosis on Intestinal Health and Function in Broiler Chickens - Kiarie, Elijah G.; Leung, Haley; Akbari Moghaddam Kakhki, Reza; Patterson, Rob; Barta, John R. (Frontiers in Veterinary Science, 2019)
The hallmark of coccidiosis is the presence of necrotic intestinal lesions that impair digestive capacity and barrier function in concurrence with increased risks for secondary bacterial infections. Concerns over the development of resistant Eimeria species to existing anticoccidials, gaps in coccidial vaccination application and restriction on antibiotics is making it imperative to explore alternative and/or complimentary strategies for coccidiosis control. The intent of this review is to appraise literature on the role of feed enzymes and yeast derivatives in modulating coccidiosis. Feed enzymes can complement endogenous enzymes (protease, amylase and lipase) that may become insufficient in coccidiosis afflicted birds. Coccidiosis in the upper small intestine creates conditions that enhances efficacy of phytase and there are reports indicating supplemental phytase can mitigate the negative impact of coccidiosis on bone quality in broiler chickens. Increase in intestinal short chain fatty acids due supplemental fiber degrading enzymes has been linked with reduced survivability of Eimeria. There is evidence whole yeast (live or dead) and derivatives are can modulate coccidiosis. Immunomudulation properties of the yeast derivatives have been shown to enhance cellular and humoral immunity in Eimeria challenge models which is critical for effectiveness of coccidial vaccination. Moreover, yeast nucleotides have been shown to be beneficial in stimulating healing of intestinal mucosal surface. Other novel work has shown that certain yeast cells can produce derivatives with anticoccidial compounds effective in attenuating oocysts shedding. Yeast cell surface has also been shown to be an effective oral Eimeria vaccine delivery vehicle. Overall, while further refinement research is warranted to address inconsistencies in responses and commercial application, there is evidence feed enzymes and yeast derivatives could complement strategies for maintaining intestinal function to bolster growth performance in broilers compromised with coccidiosis. However, in most part, feed additives evaluation and interpretation takes a simplistic view of a single additive whereas broilers often receive diets containing mix of distinct additives. It is imperative to consider evaluating combinations of additives to document animal responses and potential synergies.